Educação intercultural das encruzilhadas: possibilidades de construção da agência Sentipensante no projeto brincada - Silva, Thiago Lazaro Pereira da (2024)
The Brincadas Extension Project, which is organized by researchers from the Language in Activity Research Group in the School Context (GP-LACE), appeared as a response to the emerging demands of Covid-19 and has been working on several fronts- one of them is education. In this study, I investigated a meeting held by the project at EMEF RRN that worked on the theme “masculinities”. Taking it into account, I discuss and understand the Brincadas Project from the perspective of Interculturality and Pedagogy of the Crossroads. The objective, therefore, is to understand whether or not an Intercultural Education of Encruzilhadas can raise the Sentipensante Agency, it means an agent that acts with emotion and reason. The proposal presented is based on Interculturality (WALSH, 2007; 2009; CANDAU, 2008), Pedagogy of the Crossroads (RUFINO, 2019), Agency (ENGESTRÖM, 2006) and Sentipensante (FALS BORDA, 2015). The methodology of this study is outlined by the Critical Collaboration Research (MAGALHÃES, 2006, 2018; NININ; MAGALHÃES, 2017). For data collection and selection, transcriptions of video recordings taken from the project's digital collection were made in addition to photographic records. In data analysis, I am based on the lexical-interpretivist and multimodal perspective. The results point to an organization of training guided by Engaged Multiliteracy (LIBERALI, 2022) that allows the development of the characteristics of dialogue, cruzo, questioning power relations, facing contradictions and the collective construction of ideas and concepts to transform the unfair reality, which characterizes an Intercultural Education of Encruzilhadas. Such marks allow us to understand that subjects start to act in an emotional way, since they defend their point of view rationally, but, at the same time, with emotion and seek to strengthen the collective to fight against limiting beliefs